Differences in muscle activation between submaximal and maximal 6-Minute rowing tests - Gerzevic, M.; Strojnik, V.; Jarm, T. (The Journal of Strength and Conditioning Research, 2011)
This study aimed to establish the differences in muscle activation between a 6-minute simulated race (all-out test) and a submaximal (blood lactate [LA] concentration 4 mmol/L) 6-minute effort (submax test) on a rowing ergometer. Eleven healthy, well-trained subjects performed the submax test followed after 1-hour rest by the all-out test. Surface electromyographic (sEMG) signal of muscles gastrocnemius medialis (GC), rectus femoris (RF), vastus lateralis (VL), biceps femoris, gluteus maximus (GM), erector spinae (ES), lower latissimus dorsi (LD_lo), upper latissimus dorsi (LD_up), brachioradialis (BR) and biceps brachii (BB), and other biomechanical, biochemical, and respiratory parameters were monitored during rowing. During the all-out test, the subjects covered a longer distance with larger average power output, higher stroke frequency, LA concentration, and oxygen consumption compared to the submax test (p < 0.05). During the submax test, the average rectified values (ARVs) of sEMG signal increased significantly only in the RF and LD_lo muscles. During the all-out test, the ARVs of the RF, VL, and GM muscles increased (p < 0.05), whereas the MDFs of the RF, ES, and LD_lo muscles decreased (p < 0.05). Compared to the submax test, the ARVs of the GC, RF, VL, LD_lo, LD_up, and BB muscles were significantly higher during the all-out test. However, only for the RF muscle, the all-out test resulted in a significantly lower MDF value compared to the submax test. The most involved muscles that would need special attention in training seem to be the leg and shoulder girdle extensors and arm flexors but not the trunk and hip extensors.